2019
DOI: 10.1097/inf.0000000000002039
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Inappropriate Antimicrobial Prescriptions in a Tertiary Neonatal Intensive Care Unit After Antimicrobial Stewardship Care Bundle Implementation

Abstract: In this study, we found that ASP initiatives can be applied in neonatal populations to reduce inappropriate antimicrobial prescriptions, though a different approach may be needed among VLBW infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 35 publications
1
48
0
1
Order By: Relevance
“…A total of 118 full-text articles were reviewed, of which six were eligible for final analysis. Four articles were from the USA,12–15 one from Canada and one from Ireland 16 17. All articles fulfilled the minimum and mandatory ICROMS quality criteria (scores for each article according to the ICROMS methodology are presented in online supplementary annex 1-3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 118 full-text articles were reviewed, of which six were eligible for final analysis. Four articles were from the USA,12–15 one from Canada and one from Ireland 16 17. All articles fulfilled the minimum and mandatory ICROMS quality criteria (scores for each article according to the ICROMS methodology are presented in online supplementary annex 1-3).…”
Section: Resultsmentioning
confidence: 99%
“…Interventions in neonates only were conducted exclusively in NICUs 12 13 15–17. One article addressed interventions to the NICU, the paediatric intensive care unit (PICU) and the cardiac intensive care unit 14…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they observed a changed profile of antibiotic consumption: an increase in the use of ampicillin and gentamicin, and a decrease in the use of betalactamase inhibitors, macrolides and meropenem. 25 42 They compared a pre-ASP and a post-ASP cohort and found a reduction in inappropriate courses of therapy with meropenem, vancomycin, cefotaxim and linezolid.…”
Section: Resultsmentioning
confidence: 99%
“…Although other outcomes were not investigated in this study, it is safe to assume that with this intervention, antibiotic-related adverse events, the prevalence of resistant microorganisms, and antibiotic costs would also have decreased. Several studies have demonstrated a decrease in inappropriate antibiotic usage with the implementation of an ASP (Chrysou et al, 2018;Ting et al, 2018). Chrysou et al found that after implementing an ASP, total antibiotic use decreased by 16.7% owing to a 19.1% reduction in unrestricted antibiotics and 13.8% in restricted antibiotics (Chrysou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%